Pain-Induced Pessimism and Anhedonia: Evidence From a Novel Probability-Based Judgment Bias Test - Lecorps, Benjamin; Ludwig, Brent R.; von Keyserlingk, Marina A. G.; Weary, Daniel M. (Frontiers in Behavioral Neuroscience, 2019)
Judgment bias tests use responses to ambiguous stimuli to infer emotional states in animals. However, with repeated testing, animals can learn to recognize the previously ambiguous stimuli rendering the test less effective. We describe a novel approach to this problem. Calves (n=9) were trained in a spatial discrimination task to associate 5 locations with a specific probability of reward/punishment (Positive: 100%/0%; Near-Positive: 75%/25%; Middle: 50%/50%; Near-Negative: 25%/75%; Negative: 0%/100%). As predicted, calves showed increased latencies to touch locations that had higher probabilities of punishment and lower probabilities of reward. To validate our methodology for detecting mood changes, we followed calves in the hours after routine hot-iron disbudding, a time when animals were likely experiencing post-operative inflammatory pain. At 6 h after disbudding, when inflammatory pain was likely to peak, calves expressed increased approach latencies to the Positive, Near-Positive and Middle locations. These results suggest that calves perceived the value of the reward as being lower (i.e. anhedonia) or had lower expectations of positive outcomes (i.e. pessimism). When re-tested at 22 and 70 h after disbudding, we found no evidence of pessimism or anhedonia (i.e. latencies had returned to baseline). We conclude that our probability-based judgment bias task can detect pain-induced mood changes.